Peningkatkan Keterampilan Menulis Teks Carita Pondok Naratif dalam Pembelajaran Bahasa Sunda dengan Pendekatan Contekstual Teaching and Learning (CTL) di Kelas X SMK Pelita Alam Kota Bekasi - Amitania Ibmianur (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
The results of the study evaluation for class X students in semester 2 of SMK Pelita alam in 2021 or the 2020/2021 academic year show that students' ability to write narrative "carita pondok" is not satisfactory. For this reason, one of the efforts to optimize or improve the ability to write "carita pondok" for class X students of SMK Pelita Alam is to use the Contextual Teaching and Learning (CTL) method.This research was carried out using the Class Action Research design, the subjects of this study were students in class X even semester at Pelita Alam Vocational School in the 2020/2021 academic year with a total of 26 students on the subject matter of study materials for the Sundanese language subject. In this study, writing skills "carita pondok" narrative with a time allocation 4 times 45 minutes.This study was designed for 2 cycles (cycle 1 and cycle 2). each cycle consists of 4 stages of activity, namely planning the implementation of observation and reflection evaluation of action. The data collection instrument used was 1 observation sheet 2 assessment sheets of writing skills "carita pondok" narratives and learning outcomes.This research was carried out by researchers as teachers of Sundanese language subjects and assisted by an observer accompanying colleagues. data analysis was carried out through three stages, namely data reduction, data exposure, and conclusion.The results showed that the application of Sundanese language learning strategies with the Contextual Teaching and Learning (CTL) approach could improve students' learning process skills in a better direction with a score of 80 compared to before the action was 70Judging from the ability to write narrative "carita pondok" Based on the results of the ability test to write pondok stories in Sundanese language learning by comparing the scores achieved before the pre-action and after the action learning cycles 1 and 2 were carried out, it showed that there was an increase in a better direction than before i.e. 19%